Range extension and male description of a rare clavigerite beetle in China (Coleoptera: Staphylinidae: Pselaphinae) - Yin, Zi-Wei (Zootaxa, 2023)
The myrmecophilous clavigerite Anaclasiger zhudaiae Yin & Huang is known from a single female collected in Guangdong, southern China. Here, I report the discovery of this species in Hunan, central China, associated with Nylanderia flaviabdominis (Wang) ants, which extends its range approximately 630 km northward from the type locality. The male is described for the first time, and the habitus and other major diagnostic characters are illustrated. Ex-situ photographs of living beetles and a map showing the distribution of Anaclasiger Raffray are provided.